ENSURING THE PSYCHOLOGICAL READINESS OF CHILDREN TO EDUCATION IN RURAL PRIMARY SCHOOL AS ONE OF PRIORITY DIRECTIONS OF UPDATING THE CONTENT OF EDUCATION - V.О. Ilman (Academy of Cognitive and Natural Sciences, 2008)
In the article theoretical bases o f value and necessity of research o f problem in of psychological readiness of children to the studies at rural school.